Предмет: Алгебра,
автор: pafnut95
(4a^2+2b+b^2)*(2a+b)*(b^2-4a^2)/4a^2+4ab+b^2
Ответы
Автор ответа:
0
В задании всё верно?????????!!!!!!!!!!
Приложения:
Автор ответа:
0
(4a^2+2b+b^2)*(2a+b)*(b^2-4a^2)/(4a^2+4ab+b^2)=
=(4a^2+2b+b^2)*(2a+b)*(b-2a)(b+2a)/(2a+b)^2=
=(4a^2+2b+b^2)*(b+2a)*(b-2a)(b+2a)/(b+2a)^2=
=(4a^2+2b+b^2)*(b-2a)
Приложения:
Похожие вопросы
Предмет: Английский язык,
автор: sadik1501
Предмет: Другие предметы,
автор: nikitarybancev21
Предмет: Литература,
автор: Mansor0
Предмет: Алгебра,
автор: лове
Предмет: Алгебра,
автор: dimon098